Platinum Complexes with a Phosphino‐Oxime/Oximate Ligand. Issue 27 (5th July 2018) - Francos, Javier; Borge, Javier; Conejero, Salvador; Cadierno, Victorio
Abstract : The platinum(II) complex [PtCl2 (COD)] (2 ; COD = 1, 5‐cyclooctadiene) reacted with 1 and 2 equiv. of 2‐(diphenylphosphanyl)benzaldehyde oxime (1 ) to generate [PtCl2 κ 2 ‐( P, N )‐2‐Ph2 PC6 H4 CH=NOH] (3 ) and [Ptκ 2 ‐( P, N )‐2‐Ph2 PC6 H4 CH=NOH2 ][Cl]2 (4 ), respectively. Deprotonation of the oxime hydroxyl group of3 with Na2 CO3 led to the selective formation of the dinuclear species (µ‐O)‐[PtClκ 2 ‐( P, N )‐2‐Ph2 PC6 H4 CH=NO]2 (5 ), while the related methylated derivative (µ‐O)‐[PtMeκ 2 ‐( P, N )‐2‐Ph2 PC6 H4 CH=NO]2 (7 ) could be obtained from the direct reaction of [PtMe2 (COD)] (6 ) with the phosphino‐oxime ligand1 . In the case of4, its treatment with Na2 CO3 yielded complex [Pt(κ 2 ‐( P, N )‐2‐Ph2 PC6 H4 CH=NO2 H)][Cl] (8 ), as a result of the deprotonation of only one of the OH groups of4 . On the other hand, contrary to what was observed with6, no deprotonation of the oxime occurred in the reaction of [PtMe3 I]4 (9 ) with1, from which the mononuclear Pt IV derivative fac ‐[PtIMe3 κ 2 ‐( P, N )‐2‐Ph2 PC6 H4 CH=NOH] (10 ) was isolated. The solid‐state structures of compounds3, 4, 7 and10 were determined by X‐ray crystallography. In addition, the potential of all the synthesized complexes as catalysts for the dehydrogenative coupling of hydrosilanes with alcohols is also briefly discussed. Abstract : New mono‐ and dinuclear platinum complexes, some of them featuring high catalytic activity in the cross dehydrogenative coupling of hydrosilanes with alcohols, could be accessed by reacting the hybrid bidentate ligand 2‐(diphenylphosphanyl)benzaldehyde oxime with the Pt II and Pt IV precursors [PtCl2 (COD)] (COD = 1, 5‐cyclooctadiene), [PtMe2 (COD)] and [PtMe3 I]4 .